2019
DOI: 10.2147/ott.s198313
|View full text |Cite
|
Sign up to set email alerts
|

<p>Variability within the human <em>TERT</em> gene, telomere length and predisposition to chronic lymphocytic leukemia</p>

Abstract: Background: The human telomerase reverse transcriptase ( TERT ) gene encodes the catalytic subunit of telomerase that is essential for maintenance of telomere length. We aimed to find out whether variability within the TERT gene could be associated with telomere length and development of the disease in non-treated patients with chronic lymphocytic leukemia (CLL). Materials and methods: Telomere length, rs2736100, rs2853690, rs3395… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Our previous work showed that the S variant was more frequent in non-Hodgkin’s B-cell lymphoma patients how did not respond to treatment, as well as those with intermediate/high International Prognostic Index ( 159 ). In contrast, the S variant was less frequent in chronic lymphocytic leukemia patients with high disease stage ( 160 ).…”
Section: Tert Gene Polymorphismsmentioning
confidence: 93%
“…Our previous work showed that the S variant was more frequent in non-Hodgkin’s B-cell lymphoma patients how did not respond to treatment, as well as those with intermediate/high International Prognostic Index ( 159 ). In contrast, the S variant was less frequent in chronic lymphocytic leukemia patients with high disease stage ( 160 ).…”
Section: Tert Gene Polymorphismsmentioning
confidence: 93%
“…Genome wide association studies repeatedly identified TERT as one among the susceptibility loci for risk of CLL ( 66 , 67 ). Studies to identify SNPs in TERT and TERC associated with CLL identified the minor rs35033501 TERT variant ( 68 ), as well as the SNPs rs10936599 in TERC and rs2736100 in TERT ( 69 ) and presence of longer telomere length to be associated with CLL. Though shortening of telomere length in CLL is well characterized to be an adverse prognostic factor it should therefore be noted that telomerase activation and telomere lengthening constitute an important phase in malignant transformation.…”
Section: Tumor Microenvironment and Telomere Dysfunctionmentioning
confidence: 99%
“…Cumulative knowledge from previous studies had hyopthesisd that altered telomere homeostasis plays a possible role in bone marrow failures, leukemias and other malignancies 17 . Telomere erosion in tumor cells was found to predict worse prognosis with more advanced disease in chronic lymphocytic leukemia 18,19 , myeloma 20 and various cancers 20 . Mendelian short telomere is sufficient to promote premature age-related clonal hematopoiesis, primarily associated with MDS and AML 21 .…”
Section: Discussionmentioning
confidence: 99%